Snowball throwing learning strategy and learning motivation: keys to success in improving science learning outcomes for high class students - Mariam, Siti; Sapriati, Amalia; Suroyo, Suroyo (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2024)
Snowball Throwing is a pedagogical strategy that employs ice balls or "snowballs" to introduce new concepts or ideas to students. This approach was developed by researchers interested in enhancing the effectiveness and engagement of learning, particularly in the context of science education. Moreover, students exhibit enthusiasm toward participation in learning activities due to the engaging nature of the snowball-throwing model. This study aims to assess the impact of employing the Snowball Throwing learning model alongside students' learning motivation on their academic performance in lessons at the elementary public school 002, Air Molek 1. The study involved 172 students across 4th, 5th, and 6th grade classes, comprising 99 boys and 76 girls. Data were collected through written tests and learning motivation questionnaires. The written test comprised 20 multiple-choice questions designed to evaluate student learning outcomes, while the learning motivation questionnaire gauged the students' level of motivation toward learning. Data analysis was conducted using the two-way ANOVA test. The results of the analysis demonstrated the significant influence of learning motivation on student learning outcomes. Notably, student learning motivation positively correlates with enhanced learning outcomes. Furthermore, the adoption of the snowball-throwing learning model exhibited a beneficial impact on student learning outcomes. Additionally, the interaction between the snowball-throwing learning model and student learning motivation significantly influenced student learning outcomes. Consequently, it can be inferred that the efficacy of Snowball Throwing in education stems from its ability to bolster learning motivation and improve learning outcomes, particularly within the realm of science education.